Corporate Brand Rapture Theory: Antecedents, Processes, and Consequences - Lloyd, Stephen; Woodside, Arch (Emerald Group Publishing Limited, 2013)
Purpose – This study seeks to provide analytical insights into corporate brand-rapture (CBR), its antecedents and consequences, and contributes to methodology for modeling CBRs. Design/methodology/approach – The paper defines the construct and develops a theory that explains how corporate brand-rapture works and is testable empirically. Findings – CBR merits further investigation as a potentially valid, operational concept in marketing that underpins the conscious and unconscious drivers of the corporate brand's strongest stakeholders and that lays the foundations of research into corporate brand-rapture communication. Research limitations/implications – The paper, while remaining conceptual, identifies a dynamic concept of interest to researchers and to corporate brand marketing management and proposes seven fundamental propositions for modeling CBR. Practical implications – The paper provides researchers and corporate brand marketing with a more rigorous understanding of the foundations of engagement with a corporate brand. Originality/value – This paper is the first so far on CBR theory and provides insights that are important to corporate brand marketers and their communications strategies.